A paper-based invasion assay: Assessing chemotaxis of cancer cells in gradients of oxygen. (June 2015) - Mosadegh, Bobak; Lockett, Matthew R.; Minn, Kyaw Thu; Simon, Karen A.; Gilbert, Karl; Hillier, Shawn; Newsome, David; Li, Howard; Hall, Amy B.; Boucher, Diane M.; Eustace, Brenda K.; Whitesides, George M.
Abstract: This work describes a 3D, paper-based assay that can isolate sub-populations of cells based on their invasiveness (i.e., distance migrated in a hydrogel) in a gradient of concentration of oxygen (O2 ). Layers of paper impregnated with a cell-compatible hydrogel are stacked and placed in a plastic holder to form the invasion assay. In most assays, the stack comprises a single layer of paper containing mammalian cells suspended in a hydrogel, sandwiched between multiple layers of paper containing only hydrogel. Cells in the stack consume and produce small molecules; these molecules diffuse throughout the stack to generate gradients in the stack, and between the stack and the bulk culture medium. Placing the cell-containing layer in different positions of the stack, or modifying the permeability of the holder to oxygen or proteins, alters the profile of the gradients within the stack. Physically separating the layers after culture isolates sub-populations of cells that migrated different distances, and enables their subsequent analysis or culture. Using this system, three independent cell lines derived from A549 cancer cells are shown to produce distinguishable migration behavior in a gradient of oxygen. This result is the first experimental demonstration that oxygen acts as a chemoattractant for cancer cells.